Respuesta :

Answer:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    3*(x+15)*23-(24)=0  

Step by step solution :

STEP

1

:

Equation at the end of step 1

 (3 • (x + 15) • 23) -  24  = 0  

STEP

2

:

Equation at the end of step 2

 69 • (x + 15) -  24  = 0  

STEP

3

:

STEP

4

:

Pulling out like terms

4.1     Pull out like factors :

  69x + 1011  =   3 • (23x + 337)  

Equation at the end of step

4

:

 3 • (23x + 337)  = 0  

STEP

5

:

Equations which are never true

5.1      Solve :    3   =  0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation:

5.2      Solve  :    23x+337 = 0  

Subtract  337  from both sides of the equation :  

                     23x = -337

Divide both sides of the equation by 23:

                    x = -337/23 = -14.652

Step-by-step explanation:

ACCESS MORE